Efficacy and safety of different acupuncture therapies in treating sleep apnea syndrome: a systematic review and network meta-analysis - Yun Li; Ling Gao; Xiyan Gao; Wenming Chu; Boyu Zhang (Annals of Medicine)
Objective To evaluate and rank the efficacy and safety of different acupuncture (AP) therapies in treating sleep apnea syndrome (SAS).Methods We searched PubMed, Web of Science, Cochrane Library, Embase, Wanfang Data, CNKI, CBM, and VIP for randomized controlled trials (RCTs) studying AP for SAS until April 25, 2024. Effectiveness required a >25% decrease in apnea-hypopnea index (AHI) and a >1/3 reduction in symptom scores after treatment. Secondary outcomes included AHI, lowest oxygen saturation (LSaO₂), longest apnea time (LAT), Epworth Sleepiness Scale (ESS) score, and adverse events (AEs). We performed standard pairwise meta-analyses and network meta-analyses (NMA) using Stata15.1 and RStudio4.2.3, assessed evidence quality (GRADE), and ranked treatments using SUCRA values.Results Network meta-analysis of 43 randomized trials (3402 SAS patients) revealed distinct efficacy profiles: Electroacupuncture (EA) was the best intervention for reducing apnea-hypopnea index (AHI) (SUCRA=86.0%), while acupoint catgut embedding (ACE) ranked highest for both shortening longest apnea time (LAT) (SUCRA=98.7%) and improving lowest oxygen saturation (LSaO₂) (SUCRA = 89.7%). For reducing daytime sleepiness (ESS), manual acupuncture combined with Chinese herbal decoction (MA+OCHD) was most effective (SUCRA = 87.6%). In terms of overall clinical effectiveness rate, manual acupuncture plus Western medicine (MA+WM) performed best (SUCRA = 79.8%). Safety analysis showed Chinese herbal decoction (OCHD) alone was associated with the fewest adverse events (SUCRA = 93.4%).Conclusion AP therapies are effective and safe for SAS. EA or ACE best improves breathing parameters, MA+OCHD best reduces sleepiness, and MA+WM yields the highest overall effectiveness. These findings guide SAS treatment selection.